Do birds of a feather really flock together?: friendships, self-control similarity and deviant behaviour - Boman, John H. (The British journal of criminology, 2017)
In addition to research consistently linking self-control to crime, a person’s level of self-control is hypothesized to be the root cause of why friendships form. Namely, people with low self-control should ‘flock together’ in highly deviant friendships, and, inversely, persons with high self-control should ‘flock together’ in non-deviant friendships. Using dyadic friendship data, this study examines the extent to which self-control similarity, termed self-control ‘homophily’, exists and what implications it carries for deviance. Using hierarchical linear modelling, results demonstrate that friends’ levels of self-control are dissimilar and fail to interact in relation to crime. Instead, differences in friends’ levels of self-control may be more strongly related to crime, failing to support Gottfredson and Hirschi’s hypothesis.